(3GdTGaj aj GdEeGeIs
(3ChdgG (B:s
(3GdMeO ddg hSdGeg Ydi YHGOg GdPjf GUWai SCdJ CjOc Gddg JJHY eG EfWhi Ydjg GdcJGH GdeYQha HGdeZfi ef GdMLGL ai GdEeGeI aUd ai JJHY eG PcQg eeeG jJYdb HhLhH GdEeGeI s
(3BNQgG (B:s
(3ef GdhGLH Cf fYWa Ydi eG JbOe ef GdcJGH afTQMg djdMb HChGSWg Ch BNQg hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3Gdabg GdESdGejs